Proceedings of the First International Joint Conference on Autonomous Agents and Multiagent Systems Part 1 - AAMAS '02 2002
DOI: 10.1145/544741.544824
|View full text |Cite
|
Sign up to set email alerts
|

An architecture for emotional decision-making agents

Abstract: Our research focuses on complex agents that are capable of interacting with their environments in ways that are increasingly similar to individual humans. In this article we describe a cognitive architecture for an interactive decisionmaking agent with emotions. The primary goal of this work is to make the decision-making process of complex agents more realistic with regard to the behavior moderators, including emotional factors that affect humans. Instead of uniform agents that rely entirely on a deterministi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Research has showed that emotions have an important impact on the performance of most of our daily activities such as communication, planning, behavior and decision making (Scherer, 2005). It is assumed that emotions are the catalyst of the brain activity that directs our attention and behavior; also, they inform us of the importance of events that occur around us (Chown, Jones, & Henninger, 2002). In this section, we present our approach for behavior modeling.…”
Section: Behavior Modeling Methodsmentioning
confidence: 99%
“…Research has showed that emotions have an important impact on the performance of most of our daily activities such as communication, planning, behavior and decision making (Scherer, 2005). It is assumed that emotions are the catalyst of the brain activity that directs our attention and behavior; also, they inform us of the importance of events that occur around us (Chown, Jones, & Henninger, 2002). In this section, we present our approach for behavior modeling.…”
Section: Behavior Modeling Methodsmentioning
confidence: 99%
“…This is a clear indicator that people do not treat information neutrally. As Kaplan and others [Chown, et al 2002] have argued, the human emotional system can be understood in these terms. The argument is based upon the idea that human emotions address the need our ancestors had to make very fast decisions in encounters with other dangerous predators.…”
Section: Evolutionary and Environmental Psychologymentioning
confidence: 99%